2008
DOI: 10.1093/annonc/mdn052
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of autologous stem-cell transplantation in relapsed or refractory Hodgkin's lymphoma

Abstract: These data provide the longest follow-up reported for patients receiving ASCT for relapsed/refractory HL. In addition to previously described prognostic factors, our data show that Hasenclever index <3 influences outcome favorably and attaining CR at ASCT leads to a better outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
92
3
10

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 24 publications
6
92
3
10
Order By: Relevance
“…The standard treatment for patients with HL who are unresponsive to frontline therapy or relapse after primary treatment consists of salvage chemotherapy followed by high-dose chemotherapy and autologous stem cell transplantation (ASCT) [3][4][5][6]. Fifty percent of these patients achieve a long-term progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…The standard treatment for patients with HL who are unresponsive to frontline therapy or relapse after primary treatment consists of salvage chemotherapy followed by high-dose chemotherapy and autologous stem cell transplantation (ASCT) [3][4][5][6]. Fifty percent of these patients achieve a long-term progression-free survival (PFS).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that single ASCT can provide a cure in roughly 50% of unselected patients. 6,7 Thus, the outcome of intermediate-risk patients treated with single ASCT in our trial was better than the outcome of these unselected patients treated with single ASCT. Moreover, the outcome of poor-risk patients treated with tandem ASCT in our trial was similar to the outcome of these unselected patients treated with single ASCT.…”
Section: Discussionmentioning
confidence: 72%
“…Concerning the cumulative incidence of SPM, data from retrospective studies are difficult to interpret because of differences in median follow-up, selection of patients (all transplanted patients or only patients who survived ≥2 years after ASCT), period of inclusion, number of treatment lines before ASCT, heterogeneity of treatments, conditioning regimens and source of stem-cells. 7,[17][18][19] Given this, the cumulative incidences of SPM in retrospective studies ranged from 5.8% to 14.7% at 10 years, and from 8% to 15.3% at 15 years. In the present study, considering patients who did not relapse after completing single ASCT (intermediate-risk group), the 10-and 15-year cumulative incidences of SPM were 16% and 24%, respectively, which are higher than in retrospective studies.…”
Section: A B D Cmentioning
confidence: 98%
“…A study by Moskowitz et al reported significantly better event-free survival, progression-free survival (PFS) and overall survival (OS) after HDT/ASCT for patients responding to second-line therapy (60, 62 and 66%, respectively) when compared with those with poor responses (19,23 and 17%, respectively; p < 0.001) [12]. Sirohi et al have reported that patients who were in complete response (CR) or partial response (PR) at the time of HDT/ASCT had better 5-year OS rates (79 and 59%, respectively) when compared with those with disease that was resistant to second-line salvage chemotherapy prior to HDT/ASCT (17%; p < 0.001) [13]. Due to the generally small number of patients and the hetero geneous population enrolled in these studies, analyses comparing different salvage regimens become difficult.…”
Section: Editorialmentioning
confidence: 99%